Supervisi Pendidikan dalam Peningkatan Profesionalisme Guru - Almaajid, Rizqi; Siregar, Nurjannah; Novaliza, Aidelia; Arifandi, Ridwansyah; Oktafiana, Aisyah; Ayumi, Malika; Nasution, Inom (ANWARUL, 2023)
The low level of education in Indonesia can be caused by the low human resources in Indonesian education, namely educators or teachers who do not have professionalism in carrying out their duties. Educational supervision is one way that can be taken in improving the quality of education through career development or the professionalism of a teacher. Educational supervision leads to improvement of educational problems through guiding, supervising, guiding and directing teachers to be professional in their field to improve education and fix problems in education. Educational Supervision assists teachers in making plans in the learning process so as to produce the desired output in learning. The purpose of writing this article is to examines educational supervision in increasing teacher professionalism. The type of method for writing this article uses the literature study method, namely in the form of a series of library activities that relating to methods of gathering information, reading and taking notes, as well as managing research materials. Based on research studies, it was obtained several results that educational supervision consists of two parts, namely managerial supervision and academic supervision. Managerial supervision is in the form of educational supervision with monitoring activities carried out by high school supervisors the performance of school principals in school management, while academic supervision focuses on supervising and monitoring teacher performance in carrying out their duties. The two sections of educational supervision are interrelated, so that in order to obtain quality education through teachers who have professionalism, these two sections of educational supervision must done together.